Enhanced expression of the bacterial chloramphenicol acetyltransferase gene in mouse cells cotransfected with synthetic polynucleotides able to form Z-DNA. - Banerjee, R (1986)
Recent studies have demonstrated that the left-handed, Z-DNA conformation is favored in polymers containing alternating purine/pyrimidine sequences that can exist in vivo and may play a role in gene expression. On the basis of this assumption, we have studied the effect of various cotransfected polynucleotides on the transient expression of the chloramphenicol acetyltransferase (CAT) gene in thymidine kinase-deficient murine L cells. Cotransfections were performed by calcium phosphate coprecipitation of CAT gene plasmids with various polymers, and the CAT enzymatic activity was measured in cell lysates after 48 hr. About 2- to 10-fold stimulation of CAT gene expression was observed when the cells were cotransfected with 10 micrograms (per 10-cm culture dish) of plasmid pSV2cat, which contains simian virus 40 (SV40) promoter and enhancer sequences, and 2-10 micrograms of polymers that can form Z-DNA, such as poly(dG-m5dC) X poly(dG-m5dC) or poly(dG-dC) X poly(dG-dC), as compared to transfection with pSV2cat alone. Further, enhanced CAT gene expression was also observed when cotransfections were performed with these polymers and two other plasmid vectors, one containing the SV40 promoter but no enhancer and the other lacking any SV40 regulatory sequences. However, poly(dA-dC) X poly(dG-dT), which can form Z-DNA, did not induce any stimulation. Similarly, no or very little stimulation was observed after cotransfection of pSV2cat with either poly(dG) X poly(dC) or poly(dA-dT) X poly(dA-dT), which do not adopt the Z conformation. These results suggest that certain polynucleotides may enhance transcription of the CAT gene.